Composition and Function of Decellularized Human Lung Extracellular Matrix from Congenital Pulmonary Airway Malformation - Yanan Li; Ping Yang; Miao Yuan; Xinglong Zhu; Shengqiang Mao; Ying Yang; Menglin Yao; Fei Chen; Yanyan Zhou; Ji Bao; Chang Xu; Yi Li (Journal of Clinical Medicine, 2026)
Background: Congenital pulmonary airway malformation (CPAM) is a rare developmental disorder characterized by cystic lung lesions, yet its extracellular matrix (ECM) composition remains poorly understood. This study employed decellularization and data-independent acquisition (DIA) proteomics to compare ECM profiles between cystic (CPAM) and histologically normal non-diseased (ND) regions from the lungs of four patients. Results: The decellularized scaffolds retained their native architecture with minimal residual DNA (